Planning and Implementing a Mutually Beneficial International University Partnership in Educational Leadership Between U.S. and Middle Eastern Institutions. Issue 2 (April 2019) - Tekleselassie, Abebayehu; Ford, Angela
Responding to the forces of internationalization and globalization, universities are partnering across national borders to expand their outreach, increase capacity, expand research possibilities, and for a list of other reasons. This study looks at one international university partnership between an institution in the United States and one in the Middle East. This article examines the impetus for partnership, the steps and decisions of formation, the benefits, and challenges experienced, the lessons learned, as well as the implications and the possible paths forward. This study will provide the conceptualization and practical framework for those interested in forming international partnerships.